2022
DOI: 10.3389/fnsys.2021.807297
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Hippocampal Correlations in Environmental Enrichment During the Adolescent to Adulthood Transition in Mice

Abstract: Environmental enrichment is known to induce neuronal changes; however, the underlying structural and functional factors involved are not fully known and remain an active area of study. To investigate these factors, we assessed enriched environment (EE) and standard environment (SE) control mice over 30 days using structural and functional MRI methods. Naïve adult male mice (n = 30, ≈20 g, C57BL/B6J, postnatal day 60 initial scan) were divided into SE and EE groups and scanned before and after 30 days. Structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Widespread increases in mean diffusivity in the white matter tracts in the frontal lobes bilaterally, internal and external capsules, and partial right parietal lobe also occurred after a wellness/cognitive enhancement program in older adults ( Stephen et al, 2020 ). Environmental enrichment in mice resulted in increased mean diffusivity in the visual cortex ( Manno et al, 2022 ). Despite these results, at least one report has shown that mean diffusivity in the uncinate decreases with exercise ( Predovan et al, 2021 ), however, it is important to note that the approach used in this study used probabilistic tractography of the uncinate and not an anatomical approach that consider the unique anatomy of this pathway [the approach we used in this study, and which is based on our prior work ( Granger et al, 2021 )].…”
Section: Discussionmentioning
confidence: 99%
“…Widespread increases in mean diffusivity in the white matter tracts in the frontal lobes bilaterally, internal and external capsules, and partial right parietal lobe also occurred after a wellness/cognitive enhancement program in older adults ( Stephen et al, 2020 ). Environmental enrichment in mice resulted in increased mean diffusivity in the visual cortex ( Manno et al, 2022 ). Despite these results, at least one report has shown that mean diffusivity in the uncinate decreases with exercise ( Predovan et al, 2021 ), however, it is important to note that the approach used in this study used probabilistic tractography of the uncinate and not an anatomical approach that consider the unique anatomy of this pathway [the approach we used in this study, and which is based on our prior work ( Granger et al, 2021 )].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to perform noninvasive repeated imaging in the same animal enables us to study the longitudinal progression of diseases or treatments using these modalities. Moreover, the localization of morphological and functional changes in the organ systems of small animals provides information on embryonic development [ 20 ], genetic mutations [ 21 ], potential therapeutic treatments [ 22 , 23 ], environmental factors, and their impacts [ 24 26 ]. Preclinical research, also known as translational research, plays a critical role in the development of clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have indicated that sustained multimodal environmental enrichment (EE), combining motor, cognitive, sensory, and social stimulation, has far-reaching benefits for the brain. In animal models, groups of rats or mice exposed to EE show greater benefits compared to groups of animals with low EE (i.e., standard housing), particularly in the memory system including hippocampal structure and function ( Fabel et al, 2009 ; Kempermann et al, 2010 ; Kempermann, 2019 ; Manno et al, 2022 ). In humans, multimodal activities such as regular musical instrument playing or dancing have been associated with a reduced risk of developing dementia ( Verghese et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%